Prevalence and severity of periodontal disease in type 2 diabetes mellitus (non-insulin-dependent diabetes mellitus) patients in Bangalore city: An epidemiological study - S M Apoorva; N Sridhar; A Suchetha (Wolters Kluwer Medknow Publications, 2013)
Background: Our objective was to study the prevalence and severity of periodontal disease in type 2 diabetes mellitus (DM) patients in Bangalore city. Materials and Methods : Four hundred and eight type 2 DM patients (Study Group) and 100 non-diabetic patients (Control Group) among the age group of 35-75 years were included in the study. The study group was divided based on Glycated hemoglobin levels into well, moderately and poorly controlled. Relevant information regarding age, oral hygiene habits and personal habits was obtained from the patients. Diabetic status and mode of anti-diabetic therapy of the study group was obtained from the hospital records with consent from the patient. Community periodontal index (CPI) was used to assess the periodontal status. The results were statistically evaluated. Results : The mean CPI score and the number of missing teeth was higher in diabetics compared with non-diabetics, and was statistically significant ( P=0.000), indicating that prevalence and extent of periodontal disease was more frequent and more severe in diabetic patients. The risk factors like Glycated hemoglobin, duration of diabetes, fasting blood sugar, personal habits and oral hygiene habits showed a positive correlation with periodontal destruction, whereas mode of anti-diabetic therapy showed a negative correlation according to the multiple regression analysis. The odds ratio of a diabetic showing periodontal destruction in comparison with a non-diabetic was 1.97, 2.10 and 2.42 in well, moderately and poorly controlled diabetics, respectively. Conclusion : Our study has made an attempt to determine the association between type 2 DM (NIDDM) and periodontal disease in Bangalore city. It was found that type 2 DM (non-insulin-dependent diabetes mellitus [NIDDM]) subjects manifested relatively higher prevalence and severity of periodontal disease as compared with non-diabetics.